Phytoplankton community structure in turbid rivers and effect of turbidity on the growth of a microalga, chlorella vulgaris Beyerinck [Beijerinck] 1890 - Latib, Nur Laishatulaini (2021)
Phytoplankton is one of the primary producers of aquatic ecosystems and shapes the base of the food pyramid that supports the rest of the trophic levels such as zooplankton and fishes in aquatic food webs. Turbidity is one of the main factors that control phytoplankton growth since it is very effective in attenuating light levels below the water surface. Any perturbation that would disrupt the aquatic food chain would change the phytoplankton community structure. Escalations of turbidity in the water body would deteriorate water quality, which would, in turn, affect the phytoplankton distribution that role as the main source of a producer. This study aimed to assess the phytoplankton community structure in turbid rivers and coastal waters in Sarawak and to determine the effects of turbidity on Chlorella vulgaris growth under laboratory conditions. The study was carried out from August 2016 to June 2017 along the coastal waters in Sarawak and three major rivers; Batang Lupar and its associated coastal waters, Batang Saribas, Batang Lassa, and Mukah (coastal area). Phytoplankton samples were collected from 16 stations in three rivers and coastal waters in Sarawak and preserved using Lugol’s iodine solution and were identified and enumerated under an inverted microscope. Physico-chemical parameters including water temperature, turbidity, dissolved oxygen, salinity, and pH were measured in-situ at all sampling stations by using HydroLab multiparameter. Phytoplankton Shannon-Weiner diversity index was calculated for all stations, and multivariate analyses were used to determine the important factors controlling the phytoplankton distribution using PRIMER software version 7. Phytoplankton species composition for all sampling stations comprised mainly of diatoms, dinoflagellates, and blue-green algae, whereas a few species of green algae were also found in the rivers. A total of 135 species of phytoplankton were recorded from all stations throughout the season, with diatoms dominating all stations, both in terms of number and species. Phytoplankton composition and distribution in the estuaries were more similar to marine phytoplankton due to the tidal influences. Mukah coastal area (Mu_Coast15 and Mu_Coast16) showed the highest total phytoplankton density (50.22±3.30 x 104 cells L-1) compared to the other stations. For Batang Lupar, the estuarine station (Lu_Est1) showed the highest total phytoplankton density (4.81±0.20 x 104 cells L-1) and the lowest total phytoplankton density was recorded at Lu_Mid5 (2.30±0.03 x 104 cells L-1) where salinity was less than 10 ppt for every month except for August 2016. Batang Saribas waters were mostly saline with salinity >20 ppt even in the upstream. In this river, the highest total phytoplankton density was at the estuary (Sa_Est6) with (5.04±0.22 x 104 cells L-1) and the lowest in the upstream Sa_Mid8 (2.08±0.05 x 104 cells L-1). In Batang Lassa, the highest total phytoplankton density was at the mid-stream at La_Ups12 (5.32±0.22 x 104 cells L-1) and the lowest at La_Ups13 (1.39±0.03 x 104 cells L-1) where the salinity at both stations was low (< 2 ppt). The marine stations had the highest (p < 0.05) species density throughout the sampling period compared to the other stations in the estuaries and the rivers. Multidimensional scaling analysis based on the phytoplankton densities revealed two distinct groups. The first group consisted of the phytoplankton with high density in coastal waters area with moderate turbidity, whereas the other group consisted of the phytoplankton with low density in the rivers with high turbidity levels. A turbidity simulation study was conducted in the laboratory to understand the results obtained from the field sampling. A chlorophyte, Chlorella vulgaris was examined with five different turbidity concentrations in triplicates including 0 NTU as the control, 100 NTU, 200 NTU, 400 NTU, and 600 NTU. Microalgae pigment was measured using Shimadzu Prominence-i high-performance liquid chromatography (LC 2030). The highest number of cell densities (5.7 x 107 cell ml-1) was produced in 0 NTU on day 21. The cell density of the culture increased over time in all concentrations, except for 200 NTU, 400 NTU, and 600 NTU where cell density decreased at the early stage of the experiment. Similarly, the highest specific growth rate (0.38±0.022 μ) was achieved in 0 NTU (p < 0.05) followed by 100 NTU, 200 NTU, 400 NTU and 600 NTU. The results of the present study illustrated that although the growth performance of C. vulgaris decreased in turbidity treatments, this species showed excellent selfadaptation capabilities to cope with stress condition and capable to produce of pigments including astaxanthin, beta-carotene and lutein.